Adiwiyata Program Management at SDN 3 Muara Ciujung Timur: Governance, Participation, and Partnership - Sri Melly Mulyati; Ino Sutisno Rawita; Rinda Noviyanti (Panicgogy International Journal, 2025)
This study investigates the management of the Adiwiyata School Program at SDN 3 Muara Ciujung Timur, Rangkasbitung Sub-district, Lebak Regency, Banten Province—the first and only public primary school in Lebak Regency to attain Adiwiyata Provincial recognition. Employing a qualitative descriptive approach with a constructivist paradigm, data were collected through passive-participant observation, semi-structured in-depth interviews with twelve purposively selected informants (principal, Adiwiyata team coordinator, subject teachers, school staff, students, school committee members), and document analysis, during January–August 2017. Data were analysed using Miles et al.’s (2014) interactive model. Findings reveal that effective programme management operated across four Adiwiyata components: (1) an environmentally conscious school policy, including a 20% budget allocation from the School Activity and Budget Plan (RKAS) and revision of school vision–mission; (2) an environment-based curriculum integrating ecological values across all subjects and through the Cultivation and Crafts subject (“from waste to blessing” philosophy); (3) participatory environmental activities featuring a consistent Jumat Bersih (Friday Clean-Up) routine, monthly action on the 9th, and the innovative “environmental virus” peer-influence strategy; and (4) management of eco-friendly facilities used as dual-purpose learning media. Active student involvement was achieved through competitive three-stage selection for the Student Adiwiyata Team, school waste-bank entrepreneurship, and a zone-based duty system. School committee participation occurred at the strategic level of policy formulation and through facilitation of external partnerships with BLH Lebak, BPBD, and the Puskesmas. Success is explained by five determinants: transformational leadership, an organically formed environmental school culture, strong social capital, programme consistency, and creative resourcefulness under material constraints. These findings contribute to school management literature by demonstrating that social capital and transformational leadership can effectively compensate for material resource limitations in community-based environmental education programmes.